17. Videoconferencing in Theatre and Performance Studies - Childs, Mark; Dempster, Jay (International Review of Research in Open and Distributed Learning, 2003)
Previous reports in this series have indicated the growing acceptance of video-conferencing in education delivery. The current report compares a series of video-conferencing methods in an activity requiring precision of expression and communication: theatre and performance studies. The Accessing and Networking with National and International Expertise (ANNIE) project is a two-year project undertaken jointly by the University of Warwick and the University of Kent at Canterbury, running from March 2001 to March 2003. The project's aim is to enhance students' learning experience in theatre studies by enabling access to research-based teaching and to workshops led by practitioners of national and international standing. Various technologies have been used, particularly ISDN video-conferencing, computer-mediated conferencing, and the Internet. This report concludes that video-conferencing methods will gain acceptance in education, as academic schools themselves are able to operate commonly available technology the assistance of specialised service units.